How are we saved? : the understanding of salvation in the Orthodox tradition - Kallistos, Bishop of Diokleia, 1934- (Light & Life Pub., 1996)
An easy-to-read, easy-to-understand presentation of the Orthodox Christian way of salvation based on Scripture, the early tradition of the ancient, undivided Church, and the Church Fathers. Excellent for personal reading and study groups.